Effects of osteocytes on vibration-induced reflex muscle activity in postmenopausal women - Bahadir, Cengiz; Karamehmetoglu, Safak Sahir; Karacan, Ilhan; Cidem, Muharrem; Kucuk, Suat Hayri; Ekmekci, Hakan (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2014)
Background/aim: To assess whether osteocytes have an effect on reflex myoelectrical activity during whole-body vibration (WBV) in postmenopausal women. Materials and methods: Participants were classified into 2 groups: the low bone mineral density (BMD) group (n = 37) and normal BMD group (n = 43). Hip BMD was measured using dual-energy X-ray absorptiometry. Surface electromyography data recorded from the adductor longus muscle were processed to obtain vibration-induced reflex myoelectrical activity. Changes in plasma sclerostin (SOST) levels with WBV were expressed as a standardized vibration-induced SOST index. Results: The standardized vibration-induced SOST index was 1.03 +/- 0.24 in the low BMD group and 0.99 +/- 0.33 in the normal BMD group. For plasma SOST levels, no group-by-time interaction was found. The resting myoelectrical activities of adductor muscles increased significantly during WBV in both groups. However, there was no significant difference in the main effects of WBV on resting myoelectrical activity between the groups. The standardized vibration-induced plasma SOST index was found to be a significant independent predictor of the standardized vibration-induced reflex myoelectrical activity of the adductor muscle in both groups. Conclusion: This study suggests that osteocytes serve as mechanoreceptors of reflex electromyography during WBV.
Keywords: Plasma sclerostin protein; human; bone density; electromyography